Fixed-dose combination emtricitabine/tenofovir/efavirenz initiated during acute HIV infection; 96-week efficacy and durability. (28th November 2016) - Gay, Cynthia L.; Willis, Sarah J.; Cope, Anna B.; Kuruc, JoAnn D.; McGee, Kara S.; Sebastian, Joe; Crooks, Amanda M.; McKellar, Mehri S.; Margolis, David M.; Fiscus, Susan A.; Hicks, Charles B.; Ferrari, Guido; et al.
Abstract : Background: Updated guidelines recommend immediate antiretroviral treatment (ART) during acute HIV infection (AHI), but efficacy data on regimens during AHI are limited. Methods: We provide final data on a prospective, single-arm 96-week open-label study of once-daily emtricitabine/tenofovir/efavirenz initiated during AHI. The primary endpoint was the proportion of responders with HIV RNA less than 200 copies/ml by week 24. We examined time to viral suppression, retention, and CD8 + cell activation through week 96 in relation to baseline characteristics. Results: Between January 2005 and December 2011, 92 AHI participants enrolled. Most participants (78%) were men who have sex with men (MSM), and 42% were young MSM (18–25 years of age). Two participants withdrew leaving 90 patients for analysis. Eighty-one (90%) remained on therapy and achieved viral suppression to less than 200 copies/ml by week 24, and 71 (79%) to less than 50 copies/ml at week 48. The median time from ART initiation to suppression less than 200 copies/ml was 65 days (range 7–523) and to less than 50 copies/ml was 105 days (range 14–523). The frequency of immune activation declined from a median of 67% to 16% through week 96. Retention on study was maintained in 92% of participants at week 48 and in 83% through week 96. Among 75 participants retained through week 96, 92% were suppressed to less than 50 copies/ml. Among 39 young MSM, 79% completed a week 96 visit and 67% were suppressed at week 96. Conclusion: ART during AHI resulted in rapid and sustained viral suppression with high rates of retention in care and on ART in this cohort including a large proportion of young MSM.